2002
DOI: 10.1210/endo.143.4.8710
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Hormone Response Element Regulates Transcription of the Rat GHRH Receptor Gene

Abstract: To further elucidate the molecular mechanisms underlying the transcriptional regulation of the GHRH receptor (GHRH-R) gene, hormonal regulation of the promoter activity of this gene was examined. An approximately 3-kb genomic fragment spanning the promoter region of the gene was sequenced and the transcription start site was determined by RT-PCR and RNase protection assay. A major start site was localized at -105 (relative to the translation initiation codon, ATG), and a pit-1 binding sequence characteristic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
(56 reference statements)
4
6
0
Order By: Relevance
“…2 that the transcription from dGpG with no pit-1 site responded to DEX by 4·4-fold (Fig. 2), while it coincides well with previous results that showed that the transcription of the GHRH-receptor gene requires pit-1 (Lin et al 1992, Iguchi et al 1999, Miller et al 1999, Nogami et al 2002. The only explanation possible for this discrepancy is that some DNA sequences within dGpG-p that are absent in dGpG, the pit-1 site and the 14-base pair spacer between pGRE and the pit-1 site, contain the silencer element.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…2 that the transcription from dGpG with no pit-1 site responded to DEX by 4·4-fold (Fig. 2), while it coincides well with previous results that showed that the transcription of the GHRH-receptor gene requires pit-1 (Lin et al 1992, Iguchi et al 1999, Miller et al 1999, Nogami et al 2002. The only explanation possible for this discrepancy is that some DNA sequences within dGpG-p that are absent in dGpG, the pit-1 site and the 14-base pair spacer between pGRE and the pit-1 site, contain the silencer element.…”
Section: Resultssupporting
confidence: 90%
“…The expression plasmid for the rat GR, pit-1, and thyroid hormone receptor (TR) 2 have been described previously (Nogami et al 2002). The expression plasmid for retinoic acid receptor (RXR) was a gift from Dr Goda (Department of Nutrition, School of Food and Nutritional Sciences, University of Shizuoka, Shizuoka, Japan).…”
Section: Plasmid Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Also indicated are several of the best characterized receptor variants, although others have been reported. 186 tory element in the receptor gene promoter (Nogami et al, 2002).…”
Section: F the Growth Hormone-releasing Hormone Receptor Gene And Rementioning
confidence: 99%